A Steganographic Approach Using New Pixel Selection Combined With Hash Function for Secure Data Transmission in e-Banking - Sarkar, Atanu; Karforma, Sunil (International Journal of Computer Sciences and Engineering, 2018)
A new pixel selection technique has been introduced where data embedding starts from middle region (one or more than one pixel) of the image. Successively, diagonal pixels of middle region are selected for further embedding the data. The diagonal pixels form a quadrilateral where data are embedded through four edges of quadrilateral with clockwise manner. A hash based method is also initiated for embedding the data into the pixel of an image taking one bit position out of four LSB bits where one bit of secret data is embedded. We propose a variable hash key function for the selection of bit position so that intruder cannot guess the actual bit position of secret information easily. Our proposed method has achieved good PSNR and high capacity of secret information compared to different pixel value differencing method (PVD).